Machining Time Simulation in High Speed Hard Turning - Adesta, Erry Yulian Triblas; Al Hazza, Muataz Hazza Faizi (Trans Tech Publications, 2011)
High speed hard turning is an advanced manufacturing technology that reduces the machining time because of two reasons; reducing the manufacturing steps and increasing the cutting speed. This new approach needs an economical justification; one of the main economical factors is the machining time. The machining time was breaking down into three main parts; productive time, non productive time, and preparation time. By using MATLAB SIMULINK, a new program was developed for machining time allowing the manufacturer to find rapidly the values of cutting time parameters and gives the management the opportunity to modify the processing parameters to achieve the optimum time by using the optimum cutting parameters.